ANALYTIC NETWORK PROCESS (ANP) DAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DALAM STRATEGI PEMASARAN - Nur Avifah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This research was conducted on the CV. El Rahma Semesta which is engaged in the business of managing and selling headscarves in the city of Semarang. This CV has 3 stores namely Corner Manyaran Jilbab, Hijab Corner Sekaran (UNNES), Malika Jilbab. Based on the results of observations made on the CV. El Rahma Semesta stated that there was instability in sales at several stores, causing many items to be sold and stock buildup and the difficulty in determining the right strategy to overcome sales problems at each store. To make it easier to overcome problems and find a marketing strategy appropriately, a selection of supporting systems for selection strategies in marketing strategies using the Analytical Network Process (ANP) and Tecnic For Reference by Similarity to Ideal Solution (TOPSIS) can be used as a tool in decision making This is supported by the validation test from experts namely 3.7 which means valid. Because it lies in the validity criteria 2.51 - 3.25. and users namely 3.6 which means it is very valid because it is at a validity interval of 3.26-4.00. So this system can be used to find marketing strategies for each store.